Expression and putative roles in attachment of outer membrane proteins of Escherichia coli O157 from planktonic and sessile culture - Rivas, L.; Fegan, N.; Dykes, Gary (2008)
Many strains of Shiga toxigenic Escherichia coli (STEC), particularly the serotype O157:H7, are foodborne pathogens causing disease in many countries throughout the world. E. coli O157:H7 is able to attach and survive on various surfaces such as stainless steel (SS) found within the food processing environment. We examined the outer membrane protein (OMP) profiles of four E. coli O157 (three toxigenic O157:H7 and one nontoxigenic O157:HR) and one non-STEC strain (O1:H7), previously reported to have different abilities to attach to SS following growth in planktonic (nutrient broth) and sessile (nutrient agar) culture. The OMPs of the five E. coli strains grown in planktonic and sessile culture were extracted using N-lauroyl sarcosine and the OMP profiles were separated using two-dimensional (2D) gel electrophoresis. Qualitative and quantitative variations in the total number of OMPs expressed between planktonic and sessile cultures were found for all E. coli isolates tested. A number of differentially expressed protein spots were selected from 2D gels and were identified. FlgE was found to be expressed in planktonic culture but not sessile culture. MipA and OmpX had higher expression in sessile culture than planktonic culture, while expression of OmpA did not differ between E. coli strains or between the two modes of growth. Although differential expression of OMPs was found between isolates grown in planktonic and sessile culture, further investigations are required to determine a role of some of these identified proteins during growth of E. coli in planktonic and sessile culture and their influence during the attachment process. © Copyright 2008, Mary Ann Liebert, Inc.